HUBUNGAN MOTTO DOKTER UNTUK BANGSA DAN MOTIVASI BELAJAR DENGAN PENGALAMAN BELAJAR PADA MAHASISWA PREKLINIK FAKULTAS KEDOKTERAN UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAKARTA TAHUN 2020 - Virga Nurfitria Dewi (2021)
The development of science, technology and informatics in medicine raised high demands to master the competencies and skills in medical students, so in the process of learning the student needs encouragement that can trigger enthusiasm and determination to learn. This encouragement can be pursued through socializing the motto "doctor for the nation" and learning motivation. This quantitative study aims to determine the relationship between the motto "doctor for the nation" and learning motivation with student learning experience. This research used the cross-sectional method. The data were collected using questionnaires. The sample size was 144 respondents from medical students batch 2nd, 3rd, 4th. The univariate analysis showed that the students had a moderate perception of motto "doctor for the nation" 75,7%, moderate learning motivation 65,3%, and learning experience 70,8%. The Chi-Square test showed that there was correlation between the motto "doctor for the nation" (p value=0.001) and learning motivation (p value=0.020) with learning experiences. The multivariate showed results that the motto "doctor for the nation" has an effect of 7.17 times on the learning experience. This study showed that the motto "doctor for the nation" and learning motivation has impact to increase student's learning experience.